Small intestine volvulus Copper T complication - Cardozo, Jorge; García Pierce, Héctor; Buriano, Nelly (Cirugía del Uruguay, 1996)
The interest in this case is based on the fact that the patient presented acute abdomen as a consequence of the insertion of an intrauterine device (!UD). The complica/ion consisted of uterus perforatíon, passage to the perifonea/ cavity and penetration in the same act of an ansa of free sma/1 intestine without causing peritonitis, which as a subsequent complica/ion caused a mechanica/ process such as the volvulus of the ansa with the consequent intestinal occ/usion.